Optimization of aquaculture wastewater bioremediation and harvesting utilizing response surface methodology (RSM) - Mohd Nasir, Nurfarahana; Jusoh, Ahmad; Harun, Mohd Razif; Nik Ibrahim, Nik Nor Liyana; Wan Ab. Karim Ghani, Wan Azlina (The Italian Association of Chemical Engineering, 2021)
Microalgae are known as microorganisms which is highly concentrated with chlorophyll making them very effective bio-absorbents in treating inorganic nutrients present in the wastewater. The current study was initiated by utilizing biological-based treatment approach using microalgae, Chlorella sp. bioremediation to treat aquaculture wastewater. Bioremediation proceeds with various different pH of Chlorella sp. (pH 5- pH 10) of wastewater. While regular biomass harvesting is required for maintaining suitable biomass density and effective nutrient recycling. This study proceeded with optimization by using response surface methodology (RSM) on the evaluation of harvesting using bio-flocculant. This study proposed filamentous fungus, Aspergillus niger as sustainable bio-flocculant for that purpose. In bioremediation, the optimum inoculation dosage was recorded at 30 vol% and pH 7 with effluent concentration of ammonia 0.014 mg L-1 at Day 10. Optimum dosage, pH and mixing rate for bio-flocculation process was achieved at 30 mg L-1, pH 7 and rpm 125 with 97.2 % harvesting efficiency. The development of bioremediation with bio-harvesting would promote sustainable green technology for effective wastewater treatment.